Conocimiento y cumplimiento de medidas preventivas para neumonía asociada a ventilación mecánica, Hospital Belén de Trujillo - Baca Sánchez, Ysabel Karin (2021)
The present quantitative, descriptive, correlational, cross-sectional investigation was carried out during 2020 with the purpose of determining the relationship between the level of knowledge and the degree of compliance with preventive measures for ventilator-associated pneumonia, in its different dimensions, in nurses of the critical care unit of the Hospital Belén de Trujillo. The sample universe consisted of 47 nurses to whom a questionnaire was applied to measure the level of knowledge and a checklist to identify the degree of compliance with preventive measures, to measure the relationship between both variables the statistical test of Kendall's tau c, reaching the following conclusions: 72.3% of nurses have an excellent level of knowledge about the preventive measures of pneumonia associated with mechanical ventilation, 27.7% have a regular level of knowledge. 76.6% of nurses have an adequate degree of general compliance with the preventive measures of pneumonia associated with mechanical ventilation and 23.4% have an inadequate degree of compliance, 72.3% of nurses have an adequate degree of compliance with the preventive measures. There is a highly significant relationship between the level of knowledge and the degree of compliance with preventive measures for ventilator-associated pneumonia, achieving a Kendall's tau c value of 0.592 with a probability of 0.000.